Literature Review: Elementary Teacher's Missconception of the Social Sciences Concept and How to Grow Students' Interest in Social Studies Learning - Ashar Pajarungi Anar; Haryanto Haryanto; Muhammad Nur Wangid (Proceedings Series on Social Sciences & Humanities, 2023)
This research is a literature review to find out teachers' understanding of the correct Social Sciences concept and to find out how to foster students' interest in Social Studies learning. Based on the results of the literature review of the articles studied, it was concluded that what the teacher should do is, first the teacher must understand well what the social studies concept is like, so that the teacher can understand how to teach properly. The second is what must be taught to students, meaning that the teacher must know the subject matter to be taught so that the teacher can take the right steps on how to teach it. The third is that the teacher must know how to teach social studies so that learning is maximized, by utilizing methods, models and media that can be used in the learning process. The way that can be taken by the teacher in increasing student learning interest in social studies learning is by utilizing learning methods, models and media and not just applying lecture and rote methods that make students bored and bored with social studies learning in class. Teachers can also add references to their knowledge by reading the results of other studies so that the teacher's insight will increase.